Inner Ear Drug Delivery for Sensorineural Hearing Loss: Current Challenges and Opportunities - Liu, Sophie S.; Yang, Rong (Frontiers in Neuroscience, 2022)
Most therapies for treating sensorineural hearing loss are challenged by the delivery across multiple tissue barriers to the hard-to-access anatomical location of the inner ear. In this review, we will provide a recent update on various pharmacotherapy, gene therapy, and cell therapy approaches used in clinical and preclinical studies for the treatment of sensorineural hearing loss and approaches taken to overcome the drug delivery barriers in the ear. Small-molecule drugs for pharmacotherapy can be delivered via systemic or local delivery, where the blood-labyrinth barrier hinders the former and tissue barriers including the tympanic membrane, the round window membrane, and/or the oval window hinder the latter. Meanwhile, gene and cell therapies often require targeted delivery to the cochlea, which is currently achieved via intra-cochlear or intra-labyrinthine injection. To improve the stability of the biomacromolecules during treatment, e.g., RNAs, DNAs, proteins, additional packing vehicles are often required. To address the diverse range of biological barriers involved in inner ear drug delivery, each class of therapy and the intended therapeutic cargoes will be discussed in this review, in the context of delivery routes commonly used, delivery vehicles if required (e.g., viral and non-viral nanocarriers), and other strategies to improve drug permeation and sustained release (e.g., hydrogel, nanocarriers, permeation enhancers, and microfluidic systems). Overall, this review aims to capture the important advancements and key steps in the development of inner ear therapies and delivery strategies over the past two decades for the treatment and prophylaxis of sensorineural hearing loss.